Destination image of China’s National parks from a stakeholder perspective - Qiu Jingpei; Xie ZiXuan; Zhang Conglin (Scientific Reports)
Abstract China’s national parks are notably complex in global destination image building due to the “ecological protection first” principle, community embeddedness, and multi-stakeholder participation. Using Wuyishan National Park as a case, this study integrates text mining and grounded theory to examine: (1) destination image stakeholders, (2) interest-driven representation mechanisms, (3) systemic perception disparities, and (4) coordinated optimization pathways. The study reveals that tourists have a profound natural landscape experience but superficial cultural perception, and are sensitive to costs and management issues; residents benefit from tourism but are troubled by regional imbalances and lifestyle restrictions; enterprises seek economic benefits yet face policy constraints; the government emphasizes ecological protection and systematic governance; and non-profit organizations focus on ecological and cultural protection but are resource-constrained. This study develops a comprehensive evaluation method that integrates the perspectives of all stakeholders. Theoretically, it enriches the theoretical system of national park destination images and offers new research angles and empirical supplements to the literature. Practically, it provides collaborative image management paths for Wuyishan and experience for global national parks to balance protection and utilization in destination image building and enhancement.